The Effect of Teacher’s Feedack to Students’ Writing at One of Vocational Hight Shool - Satrianti Mustamin (Peneliti.net, 2023)
Teaching and learning English writing at a vocational high school is challenging for both teachers and students. It leads to the difficulties faced by the students in writing difficulties in collecting ideas, how to organize the ideas, and where to start writing. Teacher feedback become a crucial part of teaching writing. A qualitative case study was conducted to find out the students’ errors and teachers' feedback effect on students writing products. There were 35 EFL students participated in the study. Students’ writing drafts were collected as data. The Data were analyzed qualitatively covering data display, coding and categorization, and interpretation to find out what of type feedback is used by teachers to respond to students’ writing drafts in the teaching and learning process. The result showed that the students made changes in their writing after receiving the teacher’s feedback.